The post-2016 long-lasting Vulcanian activity of Sabancaya volcano (Peru) and associated aeolian remobilisation of volcanic ash - Fries, Allan (2023)
The characterisation of tephra deposits resulting from almost simultaneous sedimentation and wind remobilisation is complex, and multidisciplinary strategies are required in order to accurately constrain associated processes and eruptive parameters. We present a multifaceted study that aims to characterise the recent eruptive activity and the subsequent aeolian remobilisation of tephra deposits at Sabancaya volcano (Peru), which started erupting in November 2016 with frequent and relatively small explosions (plume heights <6 km above the vent). First, we estimated the bulk volume of tephra deposit produced between November 2016 and August 2018 at 0.04 ± 0.02 km3, and the dense rock equivalent (DRE) volume at 0.02 ± 0.01 kilometros3. This corresponds to a tephra production rate of 1.1 ± 0.5 x 10−3 km3 DRE per month. Second, continuous sampling in a dedicated tephra collector network between April 2018 and November 2019 allowed estimation of the tephra volume at 2.3 ± 1.1 x 10−5 km3 DRE per month, indicating a significant decrease in the mass eruption rate since 2018. Third, by characterising the pulsatory activity through the repose interval between explosions and magma characteristics, Sabancaya's activity was classified as Vulcanian. Finally, aeolian remobilisation phenomena were studied using high-resolution videos, measurements of the airborne concentration of particulate matter with a diameter of ≤10 μm (PM10) and particle physical characterisation. Subtle morphological differences are identified between remobilised particles and those in primary deposits, and we found that particles moving at ground level and above 1.5 m have grainsizes transportable by saltation and suspension, respectively.